Differences between centers in functional outcome of patients with ADHD after 1 year from the time of diagnosis - Massimo Cartabia; Stefano Finazzi; Maurizio Bonati; The Lombardy ADHD Group (Scientific Reports, 2023)
Abstract Although the pharmacological therapy of ADHD has been widely studied, little has been done to compare the different therapeutic approaches (e.g., drug therapy vs. psychological treatments) and even less has been done to compare the outcome of the therapy between centers. This multicenter observational study aims to assess between-center variation in functional outcome of ADHD patients one year after the diagnosis, according to the treatment received. We used the Regional ADHD Registry data on 1429 patients enrolled in 16 ADHD centers in the 2011–2022 period. To evaluate the effectiveness of the therapy we used a generalized linear mixed model with the center as the random effect, including patient condition at diagnosis and center characteristics, weighting by the inverse of the propensity score of the treatment received by the patient. Between-center variation was expressed as the relative difference in odds-ratios between the observed and the expected number of patients whose condition improved, using the Clinical Global Impressions—Improvement Scale (CGI-I), and the relative 95% CI. Patients who received combined treatment were significantly more likely to improve compared to other treatment groups (65.5% vs 54.4% for methylphenidate alone, 53.4% for psychological treatment alone, or 40.5% for no therapy). Adjusted for patients and center characteristics, the log-odds ratio ranged from 0.85 (0.29–1.55 95% CI) to − 0.64 (− 1.17–− 0.18 95% CI). The mean expected probability of improvement after one year of therapy for an average patient with ADHD for each center was 47.7% in a center at the 25th percentile and 61.2% in a center at the 75th percentile of the outcome distribution after adjustments. The wide between-center variation in patient functional improvement one year after the diagnosis of ADHD could be largely explained by center-specific therapeutic approaches or attitudes. More careful and stringent work is needed to reduce differences in responses between centers, as could formal and periodic audit programs within and between centers.